Implementasi Kebijakan Pajak Restoran dalam Meningkatkan Pendapatan Asli Daerah di Kabupaten Gorontalo - Zulmia Poiyo; Arifin Tahir; Alfiyah Agussalim (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to describe the following two aspects. (1) the implementation of the restaurant tax policy in increasing local own-source revenue in Gorontalo Regency, and (2) the factors that support the successful implementation of the restaurant tax policy in Gorontalo Regency. This study employs a descriptive qualitative approach. The data collection techniques include observation, interviews, and documentation. The conclusion of the findings is as follows: (1) The implementation of the restaurant tax policy in Gorontalo Regency has shown progress in planning. implementation, and supervision. However, the findings reveal that the main challenges lie in the lack of active participation from restaurant owners in policy formulation and the difficulties in adopting a more modern system; (2) Concerning the supporting factors for successful policy implementation, the findings indicate that the implementation of the restaurant tax policy in Gorontalo Regency requires attention to various interrelated factors, including clear communication, adequate resource availability, professional attitudes among policy implementers, and an efficient bureaucratic structure. Although the local government has made efforts to improve tax collection through various programs and training, deficiencies in any of these factors can reduce the effectiveness of the policy implementation.